2002
DOI: 10.1103/physreve.65.031906
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of particle size distribution in multilayered skin phantoms using polarized light spectroscopy

Abstract: We report on the ability to use polarized light to measure the particle size distribution of thin layers of polystyrene microspheres on top of a solid Intralipid phantom. The optical properties of each layer were adjusted to match the absorption and scattering properties of the epidermis (polystyrene layer) and dermis (Intralipid layer). Polarized light was used to discriminate between light scattered from the top layer of polystyrene and the lower layer of Intralipid. In this paper we also study the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…13,14 Polystyrene spheres ͑760-nm diameter͒ have strong scattering and negligible absorption in the NIR spectral range and are widely used to simulate tissue scattering. [15][16][17] Several phantoms with the same concentration of polystyrene microspheres and different concentrations of D-glucose were used in the experiments. The sphere concentrations were chosen to provide scattering coefficients s Х 50 and 100 cm Ϫ1 at ϭ 1.31 m ͑typical for tissues in the NIR spectral range͒.…”
Section: Phantomsmentioning
confidence: 99%
“…13,14 Polystyrene spheres ͑760-nm diameter͒ have strong scattering and negligible absorption in the NIR spectral range and are widely used to simulate tissue scattering. [15][16][17] Several phantoms with the same concentration of polystyrene microspheres and different concentrations of D-glucose were used in the experiments. The sphere concentrations were chosen to provide scattering coefficients s Х 50 and 100 cm Ϫ1 at ϭ 1.31 m ͑typical for tissues in the NIR spectral range͒.…”
Section: Phantomsmentioning
confidence: 99%
“…This technique was first described by Bartlet [15] to form a slurry, and sonicated. The slurry is then placed in the hot bath.…”
Section: Formulationmentioning
confidence: 99%
“…They demonstrated the feasibility of measuring the particle size distribution of internal cell structures in vitro by use of polarized light spectroscopy. 18,40 Hielscher et al 13 performed experimental study of the spatial variations of the diffuse-backscattered intensity when linearly polarized light is incident upon highly scattering media. It has been demonstrated that these polarization-dependent surface intensity maps can be used to determine the concentration, size, and anisotropy factor of the particles that constitute the scattering medium.…”
Section: Polarization Algorithmmentioning
confidence: 99%